Diagnostic value of ACR TI-RADS combined with three-dimensional shear wave elastography in ACR TI-RADS 4 and 5 thyroid nodules - Hao Lijun; Liu Peiqing; Ding Changwei; Li Jing; Zhang Yingchun (中华医学杂志英文版, 2023)
Background::Three-dimensional shear wave elastography (3D-SWE) is a promising method in distinguishing benign and malignant thyroid nodules. By combining with conventional method, it may further improve the diagnostic value. The study aimed to assess the diagnostic value of American College of Radiology (ACR) thyroid imaging reporting and data system (TI-RADS) combined with 3D-SWE in ACR TI-RADS 4 and 5 thyroid nodules.Methods::All nodules were examined by conventional ultrasonography, ACR TI-RADS classification, and 3D-SWE examination. Conventional ultrasonography was used to observe the location, size, shape, margin, echogenicity, taller-than-wide sign, microcalcification, and blood flow of thyroid nodules, and then ACR TI-RADS classification was performed. The Young’s modulus values (3D-C-Emax, 3D-C-Emean, and elastography standard deviation [3D-C-Esd]) were measured on the reconstructed coronal plane images. According to the receiver operating characteristic (ROC) curve, the best diagnostic efficiency amo